Are environmental pollution and biodiversity levels associated to the spread and mortality of COVID-19? A four-month global analysis. (15th February 2021) - Fernández, Daniel; Giné-Vázquez, Iago; Liu, Ivy; Yucel, Recai; Nai Ruscone, Marta; Morena, Marianthi; García, Víctor Gerardo; Haro, Josep Maria; Pan, William; Tyrovolas, Stefanos
Abstract: On March 12th, 2020, the WHO declared COVID-19 as a pandemic. The collective impact of environmental and ecosystem factors, as well as biodiversity, on the spread of COVID-19 and its mortality evolution remain empirically unknown, particularly in regions with a wide ecosystem range. The aim of our study is to assess how those factors impact on the COVID-19 spread and mortality by country. This study compiled a global database merging WHO daily case reports with other publicly available measures from January 21st to May 18th, 2020. We applied spatio-temporal models to identify the influence of biodiversity, temperature, and precipitation and fitted generalized linear mixed models to identify the effects of environmental variables. Additionally, we used count time series to characterize the association between COVID-19 spread and air quality factors. All analyses were adjusted by social demographic, country-income level, and government policy intervention confounders, among 160 countries, globally. Our results reveal a statistically meaningful association between COVID-19 infection and several factors of interest at country and city levels such as the national biodiversity index, air quality, and pollutants elements (PM10, PM2.5, and O3 ). Particularly, there is a significant relationship of loss of biodiversity, high level of air pollutants, and diminished air quality with COVID-19 infection spread and mortality. Our findings provide an empirical foundation for future studies on the relationship between air quality variables, a country's biodiversity, and COVID-19 transmission and mortality. The relationships measured in this study can be valuable when governments plan environmental and health policies, as alternative strategy to respond to new COVID-19 outbreaks and prevent future crises. Graphical abstract: Image 1 Highlights: National biodiversity index seems to be inversely related to COVID-19 spread. Diminished air quality was associated with increased COVID-19 spread. Air pollution was associated with increased COVID-19 spread and mortality. Abstract : Main findings: Our results reveal a relationship between COVID-19 transmission and mortality and loss of biodiversity, high level of air pollutants, and diminished air quality at country and city levels.